2013
DOI: 10.1177/0960327113476909
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based analysis of epidemiologic associations between lymphatic and hematopoietic cancers and occupational exposure to gasoline

Abstract: The presence of benzene in motor gasoline has been a health concern for potential increased risk of acute myelogenous leukemia and perhaps other lymphatic/hematopoietic cancers for approximately 40 years. Because of the widespread and increasing use of gasoline by consumers and the high exposure potential of occupational cohorts, a thorough understanding of this issue is important. The current study utilizes an evidence-based approach to examine whether or not the available epidemiologic studies demonstrate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
(166 reference statements)
0
5
0
Order By: Relevance
“…Gasoline station attendants are exposed to benzene fumes, and this exposure has been thought to lead to higher rates of lymphatic and hematopoietic cancers. 121 In support of this, one study showed a 1.6% decrease in global DNA methylation in these workers, suggesting an epigenetic mechanism of benzene action and cancer. 122 …”
Section: Environmental Toxinsmentioning
confidence: 80%
“…Gasoline station attendants are exposed to benzene fumes, and this exposure has been thought to lead to higher rates of lymphatic and hematopoietic cancers. 121 In support of this, one study showed a 1.6% decrease in global DNA methylation in these workers, suggesting an epigenetic mechanism of benzene action and cancer. 122 …”
Section: Environmental Toxinsmentioning
confidence: 80%
“…Benzene is a pervasive occupational and environmental contaminant that affects human health [1][2][3]. It is well established that exposure to benzene exposure can result in hematotoxic (including immunotoxic), genotoxic and carcinogenic (i.e., leukemogenic) effects [10][11][12]. Although its metabolism is well known, the pathogenetic mechanisms through which it exerts its toxic effect, in particular on bone marrow, are not yet well defined.…”
Section: Discussionmentioning
confidence: 99%
“…Benzene was identified as a Group 1 carcinogen and recognized by the Internationa Agency for Research on Cancer (IARC) as a human carcinogen [9], with evidence support ing its carcinogenicity (leukemia) in occupational and non-occupational settings. Its expo sure has been extensively studied and there is epidemiological and toxicological evidence showing that high exposure to benzene can lead to the development of acute myeloid leukemia (AML) and nonlymphocytic leukemia (ANLL), as well as myelodysplastic syn drome (MDS), in humans [10,11]. Furthermore, developmental, reproductive, respiratory immunological and metabolic effects have been also identified [12], although the mecha nisms of its toxicity are not entirely clear.…”
Section: Introductionmentioning
confidence: 99%
“…According to the IARC classification, benzene is a group 1 human carcinogen, causing hematological changes such as leukocytosis and lymphopenia (Giardini et al, 2023). Benzene exposure remains the main focus of public health and occupational protection measures for gasoline (Keenan et al, 2013). Although the aforementioned chemicals have been part of many toxicological studies on their own, the toxicity and risks of combined exposure to these multiple chemicals need to be evaluated in countries where there is no self-service.…”
Section: Introductionmentioning
confidence: 99%